“Resilient Young Smokers” - A Proposed Study in Determining Young Adult Smokers’ Responses Towards Anti-Smoking Initiatives in Australia - Liau, Chee How; Leanne, White; Keith, Thomas; Tan, Seng Teck (Canadian Center of Science and Education, 2018)
Although cigarette smoking rate has declined consistently in the past four decades in Australia, the smoking habit remains popular among some groups. From a marketer’s vantage point, this slowed reduction portrays the less effective implementation of anti-smoking campaigns in Australia. Ideally, each anti-smoking intervention ought to break the chain of marginal utility and lead to a sharp or stepped decline of smoking prevalence. This paper explores the inadequacies of fear factored anti-smoking campaigns and some prevailing reasons why young adult smokers continue to smoke. This paper begins with a review and categorisation of the different reasons of why young adults continue to smoke. These reasons draw on addiction, stress, habit, social-economic factors, self-identity and peer pressure. The rationale for studying these anti-smoking initiatives is to evaluate if these initiatives address the issues of smoking amongst young adults. This paper is significant for formulating effective anti-smoking messages and policy developments in Australia.